Tutorial activity as a mechanism of fses realization - V. . Adolf; N. . Pilipchevskaya (Высшее образование в России)
The authors adhere the opinion that while projecting the new educational programs it is necessary to apply education technologies, which can help students to enlarge the space of educational services. On the basis of the analysis of the contemporary trends in education theauthors formulate the concept “tutor competence” and mark out its structural components.